Effect of CeO2 Doping on Phase Structure and Microstructure of AlCoCuFeMnNi Alloy Coating - Ma,Mingxing (2019)
AlCoCuFeMnNi high-entropy alloy coating was prepared by plasma cladding method. The phase structure and microstructure of AlCoCuFeMnNi coating was investigated by XRD, SEM and EDS respectively. The results show that AlCoCuFeMnNi caotings have two BCC phase structure and typical dendrite structure and form good metallurgical bonding with substrate. The dendrite is the typical spinodal decomposition structure. After CeO2 doping, the change of peak intensity and FWHM is obvious due to the effect of Ce on the improvement of grain growth, microstructure and crystallinity. The addition of CeO2 is beneficial to reduce the cladding defect, make dendrite arm spacing enlarged and spinodal decomposition structure refined, and improve element segregation owing to the melioration effect in the temperature gradient, solidification rate, fluidity, wettability, and surface tension.